Study of the new generation NFC system and its possible applications in Ecuador - Ramírez Jiménez, Santiago (2018)
Traditionally, in the telecommunications sector worldwide, changes in its structure have been introduced over the years, as well as entry barriers to the technological world. Many state-owned companies, including Ecuadorian state-owned companies, developed their business strategies based on the monopolies of the large companies that dominate the world's technology. However, in recent years, these barriers to entry and access have gradually fallen, giving way to multiple new agents or technologies to compete in a more competitive environment.